Turbulence and Bed Load Transport in Channels With Randomly Distributed Emergent Patches of Model Vegetation. Issue 12 (13th June 2020) - Shan, Yuqi; Zhao, Tian; Liu, Chao; Nepf, Heidi
Abstract: Laboratory experiments explored the impact of vegetation patchiness on channel‐averaged turbulence and sediment transport. Stems were clustered into 16 randomly distributed circular patches of decreasing diameter. For the same channel velocity, the sediment transport increased with total stem number but decreased as stems were clustered into smaller patch diameters, occupying a smaller fraction of the bed area. The channel‐averaged turbulence, which also declined with increased clustering, was shown to be a good predictor for sediment transport at the channel scale. Previous models for uniform vegetation were adapted to predict both the channel‐averaged turbulence and sediment transport as a function of the total number of stems and degree of clustering, represented by the fraction of bed covered by patches. This provides a way for numerical modelers to represent the impact of subgrid‐scale vegetation patchiness on sediment transport. Key Points: Channel‐averaged sediment transport decreased as the total stem number decreased and as stems were gathered into smaller patches (decreasing patch diameter) For both uniform and clustered (patch) distributions of stems, the channel‐averaged sediment transport can be predicted from channel‐averaged turbulence A model was developed to predict channel‐averaged turbulence and sediment transport for randomly distributed stem patches